'The Stubborn Light of Things'. Landscape, Relational Agency, and Linear Earthworks in Later Prehistoric Britain. (2016) - Chadwick, Adrian M.
Abstract : Several regions in Britain saw the construction of large, linear earthworks of banks and ditches during the later Bronze Age and in the Iron Age, often extending for many kilometres. In the light of recent theoretical discussions of materiality and relational agency within archaeology and other social sciences, and through an avowedly discursive poetics of place, examples of these earthworks are re-assessed as actants, capable of affecting and directing the lives of people, animals, and plants. These linear earthworks were not static monuments, but were active assemblages or meshworks of materiality, movement, and memory.